Meltdown a free-market look at why the stock market collapsed, the economy tanked, and government bailouts will make things worse - Woods, Thomas E. (Washington, DC Regnery Pub. New York distributed to the trade by Perseus Distribution, 2009)
Historian Woods, writing as a libertarian, argues that government intervention in the economy actually caused the housing bubble.
The elephant in the living room -- How government created the housing bubble -- The great Wall Street bailout -- How government causes the boom-bust business cycle -- Great myths about the Great Depression -- Money -- What now?
Includes bibliographical references (p. 165-181) and index.
Keywords: Financial crises -- United States; Finance -- Government policy -- United States; Global Financial Crisis, 2008-2009.; Bailouts (Government policy); United States -- Economic conditions -- 2001-2009.; United States -- Economic policy -- 2001-2009.